2017
DOI: 10.3341/kjo.2017.0017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intracameral Bevacizumab for Treatment of Neovascular Glaucoma

Abstract: PurposeTo evaluate the long-term efficacy and safety of intracameral bevacizumab in patients with neovascular glaucoma.MethodsThis retrospective study included 26 eyes of 26 neovascular glaucoma patients who received intracameral bevacizumab injection between January 2013 and May 2015, and were followed-up for at least 1 year. All patients were treated with topical and/or systemic intraocular pressure (IOP)-lowering medications, intracameral bevacizumab, and panretinal photocoagulation (PRP). The main outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Intracameral Bevacizumab was followed-up for eight months in our study and it was considered a safe procedure for corneal endothelium. Other studies evaluated the safety of intracameral Becacizumab for NVG and found no side effects on corneal endothelim 19,20 .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Intracameral Bevacizumab was followed-up for eight months in our study and it was considered a safe procedure for corneal endothelium. Other studies evaluated the safety of intracameral Becacizumab for NVG and found no side effects on corneal endothelim 19,20 .…”
Section: Resultsmentioning
confidence: 97%
“…Other studies showed that IOP and NVI rapidly decreased after intracameral Bevacizumab but to control new vessels a single intracameral injection was not enough 2,17 . In our study, the patients received 3.45 ± 1.73 (group A) and 3.12 ± 2.10 (group B) injections, and 9 (32.1%) and 4 (40.0%) eyes received more than two injections in group A and B, respectively, similar to Ha JY et al study 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BCVA was converted to the logarithm of the minimum angle of resolution (LogMAR), and IOP was measured with a Goldmann tonometer (AT 900, Haag-Strsit AG, Switzerland, Bern) except in patients with corneal oedema due to high IOP, in whom an Icare handheld rebound tonometer (TA01i, Finland Aike company, Finland, Helsinki) was used. Iris neovascularization grades were scored as follows: grade 1, surface neovascularization of the pupillary zone of the iris involving ≤2 quadrants; grade 2, surface neovascularization of the pupillary zone of the iris involving ≥2 quadrants; grade 3, neovascularization of the ciliary zone of the iris involving 1 to 3 quadrants in addition to the pupillary zone; and grade 4, neovascularization of the ciliary zone of the iris involving ≥3 quadrants [6].…”
Section: Methodsmentioning
confidence: 99%